PERITONSILLAR ABSCESS IN CHILDREN. CLINICAL AND MICROBIOLOGICAL METHODS OF INVESTIGATION - N. V. Sirenko; S. I. Alekseyenko; G. P. Tsurikova; M. O. Volkova (Антибиотики и Химиотерапия, 2020)
70 patients with a diagnosis of paratonsillar abscess (PTA) in the age group from 2 to 17 years were treated and examined. All patients underwent surgical treatment at admission - opening of PTA under local anesthesia, followed by removal of purulent contents directly from the cavity of PTA to reveal microflora and its sensitivity. Based on the conducted study of patients with paratonzillar abscesses, surgical opening and drainage is the therapy of choice in the treatment of paratonsillar abscesses. However, antimicrobial therapy is an integral part in the complex treatment of this pathology, and prevents the development of local and systemic complications of this infection. The choice of antibiotic therapy depends on the pathogen, but at the initial stage of treatment preference should be given to broad-spectrum drugs, including antibacterial drugs of the penicillin group.